STUDY ON MICROSTRUCTURE AND PROPERTIES OF STELLITE 6/WC COMPOSITE COATING - ZHANG TianLi; ZHANG DaBing; YANG JianJun; PENG YingBiao (Jixie qiangdu)
In this paper,the Stelllite6 corrosion-resistant coating was prepared on the surface of Q960 steel plate by laser cladding technology. To improve the wear resistance of the coating,the WC powder with mass fractions of 15%,20%,30%,35% and 40% was added to the coating,respectively. The coating’s microstructure and phase were analyzed by Metallographic microscopy and X-Ray Diffraction（ XRD）. The stellite6/WC coating’s microhardness and electrochemical property were tested by microvickers hardness tester and electrochemical workstation. The results show that,with the increase of WC content,the complex phase of cobalt carbon is formed in the composite coating,and a few pores and cracks appear. The wear resistance of the composite coating is improved obviously and the corrosion resistance of the composite coating is getting worse. Comprehensive analysis of corrosion resistance and wear resistance,the stellite6 coating with 30%WC has the best comprehensive performance.